If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 2 = 23 Reorder the terms: 3(-4 + x) + 2 = 23 (-4 * 3 + x * 3) + 2 = 23 (-12 + 3x) + 2 = 23 Reorder the terms: -12 + 2 + 3x = 23 Combine like terms: -12 + 2 = -10 -10 + 3x = 23 Solving -10 + 3x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3x = 23 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 23 + 10 3x = 23 + 10 Combine like terms: 23 + 10 = 33 3x = 33 Divide each side by '3'. x = 11 Simplifying x = 11
| 2q+(-10)=108 | | 3y^2+5y-12=0 | | x-33.33x=54 | | 16y=-112 | | 5x/7+1/14+7/28 | | 16y=11 | | 2x^2+2x-96=0 | | r/3+6=42 | | 2/3x+5/6x+1/2x+10 | | -3(2x+11)=6x+33 | | 1/2(2x+3)+4x=5 | | 120=1.2x | | 2/3(4x-3)=2/5(x-4) | | 4(26-19)= | | y=x+(x*0.2) | | -11=18/5+s/5 | | 585.00+0.13x=850 | | -52-18= | | -2/3x=36 | | (p+12)/2=(8-3p)/4 | | 3y=4(2x-4) | | (-5m^6a^2/4m^-4a^-6)^-1 | | (18n^2-9n+1)/(3n-1) | | x-0.05x=418 | | 1/3(6x-9)=5 | | y=-11x-7 | | (x^2+3x-18)/(x-3) | | -4(y-7)=6y-12 | | 131.25/12.5 | | 3c-6=c+8 | | 12.5/131.25 | | (3x^2+5x+9)(6x-8)=equation |